2023
DOI: 10.1177/11786469231185102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Kynurenine/AhR Pathway in Diseases Related to Metabolism and Cancer

Amir Shadboorestan,
Meriem Koual,
Julien Dairou
et al.

Abstract: The Aryl hydrocarbon receptor (AhR) is a xenobiotic and endobiotic receptor, which regulates many cellular processes from contaminant metabolism to immunomodulation. Consequently, it is also involved in pathophysiological pathways and now represents a potential therapeutical target. In this review, we will highlight the ancestral function of the protein together with an illustration of its ligand’s battery, emphasizing the different responses triggered by these high diverse molecules. Among them, several membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…It has been established that activating AHR plays a critical role in cancer cell development, invasion, and metastasis [ 4 6 ]. Endogenous ligands of AHR include tryptophan metabolites, with the metabolism of tryptophan being mediated through two rate-limiting enzymes: TDO and IDO [ 7 , 35 ]. Recent studies suggested that interleukin-4-induced-1 (IL4I1) is more frequently associated with AHR activity than IDO1 or TDO2 [10] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been established that activating AHR plays a critical role in cancer cell development, invasion, and metastasis [ 4 6 ]. Endogenous ligands of AHR include tryptophan metabolites, with the metabolism of tryptophan being mediated through two rate-limiting enzymes: TDO and IDO [ 7 , 35 ]. Recent studies suggested that interleukin-4-induced-1 (IL4I1) is more frequently associated with AHR activity than IDO1 or TDO2 [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that interleukin-4-induced-1 (IL4I1) is more frequently associated with AHR activity than IDO1 or TDO2 [10] . Activating AHR enhances the expressions of cytochromes P450 (CYP1A1, 1A2, and 1B1), and increased levels of CYP1A1 and CYP1B1 indicate AHR activation [ 7 , 13 ]. The role of AHR in AML is controversial, with some studies suggesting that AHR activation promotes immune evasion by AML cells, while others suggest that it inhibits leukemic stem and progenitor cell (LSPC) proliferation in AML [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations